Leprosy in elderly and children among new cases - A 3-year retrospective study - Potharaju Arunraghav; Kallappa Herakal (Wolters Kluwer Medknow Publications, 2021)
Background: Leprosy occurs in all age groups, with adults constituting the majority. However, leprosy in children always drew the attention of epidemiologists as a guide to transmission of leprosy. With increasing life expectancy and decreasing prevalence of leprosy, there is going to be a significant rise of leprosy among elderly in India. In elderly leprosy patients, clinical signs are often quiet, which makes it a hidden source of infection. The detection of leprosy in elderly is of epidemiological importance, hence it is critical that due attention be given to leprosy in elderly as a possible contributor to hidden leprosy in India. Aim: To analyze leprosy in elderly and in children from the records of new patients seen over the past 3-year period. Methods: Analysis of details of "leprosy in elderly" and "leprosy in children'" from the records of new leprosy patients seen at a dermatology OPD of a teaching hospital over a period of 3 years. Results: Out of 157 patients, 34 (21.6%) were above 45 years, while 18 (11.4%) were below 15 years, the difference being statistically significant (P > 0.05). Bacteriological Index (BI) values in elderly were higher compared to children. In addition, elderly had a higher percentage of multibacillary (MB) leprosy compared to children both clinically (35% vs 22%) and histopathologically (38% vs 22%). Conclusion: Leprosy in elderly is an important entity, and there is a need to study it as a distinct group. It will provide information on hidden leprosy load and apprise us on sources of infection in the community.